Effects of insulin like growth factors on early embryonic chick limb myogenesis - Mohammed, Rabeea Hazim; Anderton, Helen; Brameld, John Michael; Sweetman, Dylan (Public Library of Science, 2017)
Limb muscles derive from pax3 expressing precursor cells that migrate from the hypaxial somite into the developing limb bud. Once there they begin to differentiate and express muscle determination genes such as MyoD. This process is regulated by a combination of inductive or inhibitory signals including Fgf18, retinoic acid, HGF, Notch and IGFs. IGFs are well known to affect late stages of muscle development and to promote both proliferation and differentiation. We examined their roles in early stage limb bud myogenesis using chicken embryos as an experimental model. Grafting beads soaked in purified recombinant IGF-I, IGF-II or small molecule inhibitors of specific signaling pathways into developing chick embryo limbs showed that both IGF-I and IGF-II induce expression of the early stage myogenic markers pax3 and MyoD as well as myogenin. Their effects on pax3 and MyoD expression were blocked by inhibitors of both the IGF type I receptor (picropodophyllotoxin, PPP) and MEK (U0126). The PI3K inhibitor LY294002 blocked IGF-II, but not IGF-I, induction of pax3 mRNA as well as the IGF-I, but not IGF-II, induction of MyoD mRNA. In addition SU5402, an FGFR/ VEGFR inhibitor, blocked the induction of MyoD by both IGFs but had no effect on pax3 induction, suggesting a role for FGF or VEGF signaling in their induction of MyoD. This was confirmed by in situ hybridization showing that FGF18, a known regulator of MyoD in limb myoblasts, was induced by IGF-I. In addition to their well-known effects on later stages of myogenesis via their induction of myogenin expression, both IGF-I and IGF-II induced pax3 and MyoD expression in developing chick embryos, indicating that they also regulate early stages of myogenesis. The data suggests that the IGFs may have slightly different effects on IGF1R signal transduction via PI3K and that their stimulatory effects on MyoD expression may be indirect, possibly via induction of FGF18 expression.